2014
DOI: 10.1186/1749-8090-9-84
|View full text |Cite
|
Sign up to set email alerts
|

Performance of steroid eluting bipolar epicardial leads in pediatric and congenital heart disease patients: 15 years of single center experience

Abstract: ObjectiveCardiac pacing is sometimes required for patients with congenital heart disease for various reasons. Because of complex anatomy, repetitive previous heart surgery and patient size, epicardial leads are of special importance in these patients. Using epicardial leads has been discussed controversly regarding pacing performance and lead survival. The aim of this study was to review the long-term data on pacing performance as well as lead survival of epicardial leads implanted in our center.MethodsRetrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 14 publications
1
13
2
Order By: Relevance
“…Two bipolar, steroid-eluting epicardial leads (Medtronic 4968, Medtronic Inc., Minneapolis, MN, USA; or St. Jude Medical 1084T lead, St. Jude Medical Inc., St Paul, MN) were placed on the posterolateral wall of the RV in a position where sensing, pacing, and impedance measurements were satisfactory. [16][17][18][19] The device was programmed before lead connection to DDIR mode. The 2 ventricular leads were connected to the generator, 1 to the atrial port and the other to the ventricular port (lack of an atrial lead precluded maintenance of AV synchrony).…”
Section: Extraction and Epi Pacing (Center 2)mentioning
confidence: 99%
“…Two bipolar, steroid-eluting epicardial leads (Medtronic 4968, Medtronic Inc., Minneapolis, MN, USA; or St. Jude Medical 1084T lead, St. Jude Medical Inc., St Paul, MN) were placed on the posterolateral wall of the RV in a position where sensing, pacing, and impedance measurements were satisfactory. [16][17][18][19] The device was programmed before lead connection to DDIR mode. The 2 ventricular leads were connected to the generator, 1 to the atrial port and the other to the ventricular port (lack of an atrial lead precluded maintenance of AV synchrony).…”
Section: Extraction and Epi Pacing (Center 2)mentioning
confidence: 99%
“…The 5-year lead survival is similar to transvenous pacing in older children, and similar or better than epicardial steroid-eluting leads in older children. [19][20][21][22] Thus, lead survival even in small children-a challenging setting with a rapidly growing child-is encouraging. At a median 14.3 years of pacing, 7 patients continued with their original leads, suggesting that the atrial loop at the initial implant allowed somatic growth and contributed to the long pacing lead survival.…”
Section: Discussionmentioning
confidence: 99%
“…Tomaske et al 20 showed excellent sensing and pacing thresholds with bipolar steroid-eluting epicardial leads in children (<18.5 years) followed up to 12 years with ventricular lead survival of 85% at 5 years. Paech et al 21 recently reported a single-center experience of 158 steroid-eluting bipolar epicardial leads in 82 children and adults with congenital heart disease-median follow-up of 3.3 years. Lead survival at 5 years was reported to be 93%.…”
Section: Discussionmentioning
confidence: 99%
“…This type of lead reduces stimulation thresholds by suppressing post-implant inflammation, and it has been shown that performance is comparative to that of endocardial leads. 3, 4 Papadopoulos et al 5 have also reported a long-term clinical outcome of steroid-eluting epicardial lead pacing in 45 children with mean follow-up of 5.7 years. The outcome was favorable, with minimal lead complications (5 lead fractures in total) and stable ventricular and atrial pacing thresholds.…”
Section: Article P 2972mentioning
confidence: 99%